Instruments of authority: Tycho Brahe's technological illustrations. (2nd October 2018) - Perkins, Emma
ABSTRACT: The astronomical instruments of Danish astronomer, Tycho Brahe, were crucial to his intended reform of astronomy in the sixteenth century. Tycho represented these devices in a series of images that were circulated in range of contexts, thereby disseminating information about his technology to a wider audience. Through an analysis of the iconographical content of these images and a consideration of the ways in which they were circulated, this article argues that images of technology were in fact crucial to Tycho's attempts to establish his authority as an astronomer. Embodying his claims to accuracy and recruiting trust in his innovative instruments, the images reinforced the validity of his astronomy and thereby played a central role in sustaining his reputation as an astronomer. Graphical Abstract: